2020
DOI: 10.1101/2020.09.07.286666
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UVA radiation could be a significant contributor to sunlight inactivation of SARS-CoV-2

Abstract: Past experiments demonstrated SARS-CoV-2 inactivation by simulated sunlight; models have considered exclusively mechanisms involving UVB acting directly on RNA. However, UVA inactivation has been demonstrated for other enveloped RNA viruses, through indirect mechanisms involving the suspension medium. We propose a model combining UVB and UVA inactivation for SARS-CoV-2, which improves predictions by accounting for effects associated with the medium. UVA sensitivities deduced for SARS-CoV-2 are consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…54 ). Particularly, the comparison between predictions ( 13) and actual measurements of Covid-19 exposure to artificial Solar radiation ( 54), suggested the importance of UV-A photons ( 16,17 ). Ratnesar-Schumate and collaborators ( 54) found that 6.8 min of continuous exposure of dried saliva-like concentrations of Covid-19 to simulated sunlight in summer at a latitude of 40 degrees were sufficient to inactivate 90% of virions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 ). Particularly, the comparison between predictions ( 13) and actual measurements of Covid-19 exposure to artificial Solar radiation ( 54), suggested the importance of UV-A photons ( 16,17 ). Ratnesar-Schumate and collaborators ( 54) found that 6.8 min of continuous exposure of dried saliva-like concentrations of Covid-19 to simulated sunlight in summer at a latitude of 40 degrees were sufficient to inactivate 90% of virions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, about 10% of the photons emitted by the Sun in the range 290-315 nm (UV-B) and as much as 95% of those in the range 315-400 nm (UV-A), reach the Earth. The effect of these photons on Single-and Double-Stranded RNA/ DNA viruses [10][11][12][13] and the possible role they play on the seasonality of epidemics [14][15][16][17][18][19][20][21][22][23][24][25] , are nevertheless little studied and highly debated in alternative or complementarity to other environmental causes 23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] . Notably though, the effects of both direct and indirect radiation from the Sun needs to be considered in order to completely explain the effects of UV radiations in life processes (with e.g.…”
mentioning
confidence: 99%
“…[54]). Particularly, the comparison between predictions ( [13]) and actual measurements of Covid-19 exposure to artificial Solar radiation ( [54]), suggested the importance of UV-A photons ( [16,17]). Ratnesar-Schumate and collaborators ( [54]) found that 6.8 minute of continuous exposure of dried saliva-like concentrations of Covid-19 to simulated sunlight in summer at a latitude of 40 degrees were sufficient to inactivate 90% of virions.…”
Section: S1 Of Si)mentioning
confidence: 99%
“…In particular, about 10% of the photons emitted by the Sun in the range 290-315 nm (UV-B) and as much as 95% of those in the range 315-400 nm (UV-A), reach the Earth. The effect of these photons on Single-and Double-Stranded RNA/DNA viruses [10][11][12][13] and the possible role they play on the seasonality of epidemics [14][15][16][17][18][19][20][21][22][23][24][25], are nevertheless little studied and highly debated in alternative or complementarity to other environmental causes [23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Notably though, the effects of both direct and indirect radiation from the Sun needs to be considered in order to completely explain the effects of UV radiations in life processes (with e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Les UV-A pourraient inactiver le SARS-CoV-2 par analogie au SARS-CoV-1 [ 48 ]. Cependant, Luzzatto-Fegiz et al recommandent la mise en place de recherches plus poussées et axées sur l’impact des UV-A dans l’inactivation du SARS-CoV-2 [ 48 ].…”
Section: Viabilité Du Sars-cov-2 Dans Le Milieu Aquatiqueunclassified